Competitiveness to Support the National Defense System - Setia, Adang; Purwowidagdo, Sapto J. (The Republic of Indonesia Defense University, 2015)
The purpose of this research is to identified competitiveness Indonesian Aerospace Inc. (IAe) to support the national defense system. This research is a descriptive with qualitative interview as method and using the theory of reference are: (1) Five Forces Porter; (2) Design School Mintzberg; (3) Core Competence and Resource base strategy. IAe is currently on the process of organizational transformation, the finding also suggest competitiveness can be said to be low. But there is a potential factor that causes IAe competitive advantage in the industry to improve the future development IAe and contribute to the realization of the national defense system.